Developing an Integrated Framework to Assess the Sustainability Potential of Alternative Fuels - A Life Cycle Approach - Hoque, S M Najmul (Curtin University, 2021)
This PhD project delivers a framework for the sustainability assessment of alternative fuels. The proposed framework employs the triple bottom line approach to assess the environmental and socioeconomic performance of fuels for the transport sector. The developed framework overcomes the deficiencies in the previous studies that are not capable of addressing the interdependences among the environmental, social and economic performance indicators. The framework provides a comprehensive tool for developing environmentally-friendly and sustainable socioeconomic energy policies.